2002
DOI: 10.1002/mc.10035
|View full text |Cite
|
Sign up to set email alerts
|

Frequent microsatellite instability in lung cancer from chromate‐exposed workers

Abstract: Although chromium has been the most extensively investigated metal with respect to mutagenicity and carcinogenicity, its genetic effects in humans are only partly understood. Our previous study demonstrated that lung cancer from chromate-exposed workers infrequently (20%) displayed p53 gene mutations as well as a particular mutation pattern. In the present study, we examined the replication error (RER) and loss of heterozygosity (LOH) in 38 lung cancers from 28 chromate-exposed workers (chromate lung cancer gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
80
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 28 publications
2
80
0
Order By: Relevance
“…27,28 There was no significant difference in loss of heterozygosity (LOH) at 3p between chromate-induced lung carcinomas and non-chromate-induced lung carcinomas. 13 In contrast, the frequency of RER in chromate-induced lung carcinomas (78.9%) was significantly higher than in non-chromate-induced lung carcinoma (15.4%). 13 Sozzi et al 29 reported that MSI was found not only in lung carcinoma (32%) but also in normal epithelia (36%).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…27,28 There was no significant difference in loss of heterozygosity (LOH) at 3p between chromate-induced lung carcinomas and non-chromate-induced lung carcinomas. 13 In contrast, the frequency of RER in chromate-induced lung carcinomas (78.9%) was significantly higher than in non-chromate-induced lung carcinoma (15.4%). 13 Sozzi et al 29 reported that MSI was found not only in lung carcinoma (32%) but also in normal epithelia (36%).…”
Section: Discussionmentioning
confidence: 78%
“…13 In contrast, the frequency of RER in chromate-induced lung carcinomas (78.9%) was significantly higher than in non-chromate-induced lung carcinoma (15.4%). 13 Sozzi et al 29 reported that MSI was found not only in lung carcinoma (32%) but also in normal epithelia (36%). Wistuba et al 30 reported a progressive increase in LOH frequency according to increasing severity of histopathologic changes in squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations